2020
DOI: 10.5465/amj.2018.0290
|View full text |Cite
|
Sign up to set email alerts
|

Being Different, Being Absent? A Dynamic Perspective on Demographic Dissimilarity and Absenteeism in Blue-Collar Teams

Abstract: This study offers a new theoretical and empirical perspective on the dynamic effect of demographic dissimilarity on absenteeism behavior by team members over time. Integrating social identity theory with the theory of anchoring events (i.e., key social interactions), we propose that individual absenteeism behavior depends on the relational dissimilarity to the team age and gender. Using a sample of 2,711 individual newcomers in 820 blue-collar teams tracked over seven years, we show that gender and age dissimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 114 publications
(165 reference statements)
0
21
0
Order By: Relevance
“…These findings correspond with the three stages of the anchoring model wherein the employees (1) judge the exchange event (i.e., perceived effectiveness and training climate, as mentioned) and the exchange relationship (i.e., organizational justice), (2) use this judgment, rather than moment-to-moment monitoring of exchanges, to guide future social exchange behaviors (i.e., engagement, performance, and intent to return predicted by initial perceived onboarding effectiveness), and (3) consistently view the relationship in this way over time (i.e., low psychological contract breach). Given that the second stage (Bagger & Li, 2014;Reinwald & Kunze, 2020), including over-time effects (Pathki et al, 2020), has received some empirical backing, the novel contribution of our results to the anchoring model includes support for the evaluation and durability stages, one and three.…”
Section: Theoretical Implicationsmentioning
confidence: 78%
See 3 more Smart Citations
“…These findings correspond with the three stages of the anchoring model wherein the employees (1) judge the exchange event (i.e., perceived effectiveness and training climate, as mentioned) and the exchange relationship (i.e., organizational justice), (2) use this judgment, rather than moment-to-moment monitoring of exchanges, to guide future social exchange behaviors (i.e., engagement, performance, and intent to return predicted by initial perceived onboarding effectiveness), and (3) consistently view the relationship in this way over time (i.e., low psychological contract breach). Given that the second stage (Bagger & Li, 2014;Reinwald & Kunze, 2020), including over-time effects (Pathki et al, 2020), has received some empirical backing, the novel contribution of our results to the anchoring model includes support for the evaluation and durability stages, one and three.…”
Section: Theoretical Implicationsmentioning
confidence: 78%
“…Finally, the new relationship state persists because the anchoring event, as an autobiographical memory, defines the relationship such that people attend to information that confirms their existing perceptions and disregard disconfirmatory information (Greenwald, 1980). Of the limited research that substantially applies the anchoring model, most studies find support for stage 2 of the anchoring model wherein a salient event sets the tone for future social exchange behaviors (e.g., family-supportive supervision predicts greater leader-member exchange, Bagger & Li, 2014; discrimination positively predicts absenteeism, Reinwald & Kunze, 2020). One study by Pathki et al (2020) demonstrated the lasting emotional consequences of an anchoring event (i.e., leadermember exchange), but the evaluation stage (stage 1) and durability/resistance to change stage (stage 3) require greater attention as does connection of all three stages as a reaction to an anchoring event.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 2 more Smart Citations
“…We used two control variables that we expected to be associated with emotional exhaustion and absences: gender and age. Many studies have provided evidence of linear and curvilinear relationships between these two variables and absences (Ng & Feldman, 2008; Reinwald & Kunze, 2020), as well as emotional exhaustion (Purvanova & Muros, 2010). We also included three work demands that are likely to affect levels of emotional exhaustion and absences in the cleaning industry: the total number of hours worked per month, repetitive work (one item: “I always repeat the same tasks”), and pace of work (one item: “I have to work too fast at the client’s office”), both measured with a Likert scale ranging from 1 ( strongly disagree ) to 5 ( strongly agree ).…”
Section: Methodsmentioning
confidence: 99%